2018
DOI: 10.1021/acsmedchemlett.8b00539
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Selectivity of 5-Fluorouracil Using a Reactive Oxygen Species-Activated Prodrug Approach

Abstract: We report the design, synthesis, and evaluation of novel 5-fluorouracil (5FU) prodrugs 1a,1b that are efficiently activated by the high level of reactive oxygen species (ROS) in cancer cells. Prodrugs 1a,1b selectively kill cancer cells over normal cells and are well-tolerated in mice. The strategy described herein can extend application of chemotherapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…This is distinctively different from many published reports that the entire benzylboronic acid/ester group would be lost after H 2 O 2 treatment. 18,20,[22][23]25 Previously Rokita group and Peng group have shown that the substituents on o-quinone methide (o-QM) precursors strongly affect o-QM's formation and reactivity [32][33][34] . In the case of CQB, we suspect the strong electron deficiency of quinazolinone scaffold as well as the conjugation of CQ with methylene phenol at amide bond prevents its removal.…”
Section: Cqb Can Be Cascade-activated By Ros and Tyr In Aqueous Buffermentioning
confidence: 99%
“…This is distinctively different from many published reports that the entire benzylboronic acid/ester group would be lost after H 2 O 2 treatment. 18,20,[22][23]25 Previously Rokita group and Peng group have shown that the substituents on o-quinone methide (o-QM) precursors strongly affect o-QM's formation and reactivity [32][33][34] . In the case of CQB, we suspect the strong electron deficiency of quinazolinone scaffold as well as the conjugation of CQ with methylene phenol at amide bond prevents its removal.…”
Section: Cqb Can Be Cascade-activated By Ros and Tyr In Aqueous Buffermentioning
confidence: 99%
“…Further reaction of the -SOH group with nearby a cysteine leads to disulfide bond formation and/or result in changes in the structure and function of various proteins. 99 Recently, Ai et al 103 concentrations used in all these in vitro experiments were on the high side. Prodrug 54a was tested in wild-type C57BL/6 male mice for safety.…”
Section: Thiol-sensitive Linkersmentioning
confidence: 99%
“…Recently, Ai et al 103 designed boronic acid‐ and boronate‐based prodrugs of 5‐fluorouracil (5‐FU). 5‐FU is generally used to treat solid tumors of the breast, stomach, colon, and pancreas.…”
Section: Reactive Oxygen Species (Ros) Sensitive Linkersmentioning
confidence: 99%
“…For the past 70 decades, fluoropyrimidine 5-fluorouracil (5FU) has been widely utilized as a frontline medication for the treatment of a wide variety of tumors, including colon, cervical, lung, and breast cancers. When given intravenously, it is aqueous soluble and stable (De Luca et al, 2016 ; Ai et al, 2019 ; Dai et al, 2020 ; Moorkoth et al, 2021 ). However, for early colorectal cancer, 5FU has a response rate ∼15%, and its biocompatibility decreases life times.…”
Section: Introductionmentioning
confidence: 99%